Pengaruh Parenting involvement Terhadap Perkembangan Kognitif Anak Autis di Sekolah Austis - Atik Badi'ah; Heru Santoso Wahito Nugroho; Ni Ketut Mendri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The condition of autism results in the inhibition of the achievement of children's cognitive development. This study aims to analyze the effect of parenting involvement on the cognitive development of autistic children in autistic schools. The design of this research is pretest-posttest with control group. Observations were made twice, namely to determine the cognitive development of autistic children before and after being given parenting involvement. Data were analyzed using paired sample t-test and Wilcoxon test. The results of the analysis show that the value of p = 0.000. Furthermore, it was concluded that there was an influence of parenting involvement on the cognitive development of autistic children in autistic schools.Keywords: autism; child; parenting involvement; cognitive development ABSTRAK Kondisi autisme berakibat pada terhambatnya pencapaian perkembangan kognitif anak. Penelitian ini bertujuan untuk menganalisis pengaruh parenting involvement terhadap perkembangan kognitif anak autis di sekolah autis. Rancangan penelitian ini adalah pretest-posttest with control group. Observasi dilakukan dua kali yaitu untuk mengetahui perkembangan kognitif anak autis sebelum dan sesudah diberikan parenting involvement. Data dianalisis menggunakan paired sample t-test dan Wilcoxon test. Hasil analisis menunjukkan bahwa nilai p = 0,000. Selanjutnya disimpulkan bahwa ada pengaruh parenting involvement terhadap perkembangan kognitif anak autis di sekolah autis.Kata kunci: autisme; anak; Parenting involvement; perkembangan kognitif